Treatment of a Fracture-dislocation of the Ankle Using RALCA® External Fixator - Yaniel Truffin Rodriguez; José Julio Requeiro Molina; Gerardo Águila Tejeda (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
The association of ankle fractures with a dislocation modifies their therapeutic management since the joint must not remain in such abnormal position for more than six hours and therefore, urgent surgical treatment is needed. The case of a 30-year-old woman treated at the Dr. Gustavo Aldereguía Lima Hospital in Cienfuegos is presented. The patient presented with a severe fracture-dislocation of the right ankle with a supra-syndesmotic fibular fracture, a syndesmotic injury, a deltoid ligament injury and a tibial plafond fracture resulting from a bicycle fall. The fracture-dislocation was stabilized by using a RALCA® external mini-fixator. Full recovery was achieved five months after surgery. In our service, we may not have the devices most commonly used for fixation of ankle injuries at a given moment; therefore, external fixation becomes a viable option to correct this type of fractures. For this reason, we decided to present this case that demonstrates the effectiveness of the RALCA® external fixator.